Produção e caracterização de anticorpos monoclonais contra Campylobacter fetus subsp. Venerealis - Telma Maria Alves (2006)
Myeloma cells Sp2/0-Ag14 and spleen cells from BALB/c mouse immunized with sonicated Campylobacter fetus subsp. venerealis NCTC 10354 were fused with polyethylene glycol (PEG) for the production of monoclonal antibodies (MAb's). Clones were obtained by limiting dilution and screened for specific MAb's to C. fetus subsp. venerealis NCTC 10354 by indirect ELISA and western blot against a panel of bacteria: C. fetus subsp. venerealis NCTC 10354, C. fetus subsp fetus ADRI 1812, C. sputorum biovar sputorum LMG 6647, C. lari NCTC 11352, and Arcobacter skirrowii LMG 6621 for the ELISA and C. fetus subsp. venerealis NCTC 10354 and C. sputorum biovar sputorum LMG 6647 for the western blotting. Fifteen clones producing MAb's anti C. fetus subsp. venerealis of the IgM (1) and IgG (14) classes were further screened for species-specificity. Four clones of the 15 obtained were producers of species-specific MAb's, 2 were specific for C. fetus subsp venerealis and 2 specific for C. fetus subsp fetus. None of the clones were reactive against C. sputorum biovar sputorum LMG 6647. All clones recognized a protein with molecular mass of approximately 148 kDa from lised C. fetus subsp. venerealis NCTC 10354.